Outward Foreign Direct Investment (OFDI) drivers in developing economies: a case of Malaysia / Rosfadzimi Mat Saad, Abd Halim Mohd Noor, Abu Hassan Shaari Md Nor - Mat Saad, Rosfadzimi; Mohd Noor, Abd Halim; Md Nor, Abu Hassan Shaari (2012)
Foreign direct investment, FDI in the area of globalization are no longer limited to the developed nations. Increasingly FDIs between developing countries are rivalling traditional FDIs. Outward Foreign Direct Investment, OFDI is one of the measures to indicate the performance and capability of developing countries enterprises. Malaysia as a developing economy is undertaking OFDI due to the limitation of local resources and to search for new markets. Multinational corporations, MNCs seek from other countries mainly for cheap labour, low resource prices, and new market for their products and services. This paper studies the determinants of OFDI by Malaysian based MNCs. It focuses on the factors that push off Malaysian firms to involve in OFDI such as market size, cost of skilled labour and the availability of natural resources. The period under study is from 1980 to 2008. Simple multiple regression analysis is used in the study. Export and productivity levels are found to have significant impact on OFDI.